2020
DOI: 10.1097/pec.0000000000002229
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pediatric Multisystem Inflammatory Syndrome During the COVID-19 Pandemic

Abstract: In late March and early April, New York City was an epicenter of the COVID-19 pandemic. Citizens were ordered to stay at home to flatten the curve. The adult population was affected with a severe respiratory illness as well as acute kidney injury, cardiomyopathy, arrhythmia, and thromboembolism. Although children were not affected in the same manner, weeks after the peak, reports from other countries emerged about cases of pediatric patients presenting with a novel inflammatory syndrome. We present 4 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Nine studies reported pro-BNP and BNP values (lowest median value of 410pg/ml and 120pg/ml, respectively). 11,13,19,32,33,35,37,40,41 Coagulation parameters as D-dimers and fibrinogen were reported in 27 studies with elevated median values in all patients. D-dimers median values were above 250ng/ml or 0.4mcg/ml and fibrinogen median values ranging from 503-931mg/dl.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies reported pro-BNP and BNP values (lowest median value of 410pg/ml and 120pg/ml, respectively). 11,13,19,32,33,35,37,40,41 Coagulation parameters as D-dimers and fibrinogen were reported in 27 studies with elevated median values in all patients. D-dimers median values were above 250ng/ml or 0.4mcg/ml and fibrinogen median values ranging from 503-931mg/dl.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…The age at onset was reported in all included studies, except one. 32 Children were between one month to 21 years-old, including 24 infants and median age was nine years-old in most studies. 62% were male, with a male:female ratio of 1.6:1.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations